Las fincas indigenas bribri y cabecar de Talamanca, Costa Rica - Orozco, L.=700 1 Villalobos, M.; Ortiz, A; Riascos, L.; Mendez, J.
(Es, En)
ilus., 18 ref.
Keywords: AGROFORESTERIA; CEDRELA ODORATA; CORDIA ALLIODORA; ARBOLES FRUTALES; ARBOLES MADERABLES; HOGARES; THEOBROMA CACAO; USOS; SUELO; COSTA RICA